POST-PANDEMIC HIGHER EDUCATION - LM Luvalo (Social Sciences and Education Research Review)
The COVID-19 pandemic has disrupted higher education institutions worldwide, forcing a sudden shift to online learning and remote work. It is crucial to think back on the lessons learned and re-imagine the future of higher education as the crisis begins to subside. Most studies tend to focus on the challenges that were brought by the pandemic in institutions of higher learning. This article investigated the main challenges faced by people in the field and offered innovative approaches and answers for post-epidemic higher education. It explores the potential of technology to change teaching and learning processes, the value of adaptability and resilience in educational institutions, and the part multidisciplinary collaboration plays in tackling challenging global issues. A systematic review of peer-reviewed academic articles published between January 2020 and December 2021 was conducted. A total of 12 articles were selected according to the exclusion criteria. The article proposes a plan for reimagining higher education, using the theory of 'pandemic as a portal 'which considers the lessons learned from the pandemic and is aimed at creating a system better able to cope with new challenges in an equitable yet student-centered way, drawing on data derived from international case studies and emerging trends.